Herbal remedies and anticoagulant therapy - Samuels, Noah (Thrombosis and Haemostasis, 2005)
Herbal remedies, considered to be both safe and effective by most consumers, may interact with conventional drugs.Warfarin, a vitamin K antagonist originally derived from the sweet clover plant, has a narrow therapeutic window which can be monitored using prothrombin international normalized ratios (PT-INR). Many herbs can increase the risk for bleeding when combined with warfarin, either by augmenting the anticoagulant effects of the drug (with increased PT-INR levels) or through intrinsic anti-platelet properties (without altering PT-INR levels). The increased risk for bleeding among such patients may be difficult to predict, especially when formulas which contain many herbs are used. Further research into herb-drug interactions is warranted, as are guidelines for the use of herbal remedies by patients on chronic anticoagulation therapy.
Keywords: Herbs; warfarin; anticoagulation; antiplatelet; bleeding